Arthropod damage in corn across site-specific management zones and differing water and nitrogen levels - Davidson, Silas Andrew, author; Peairs, Frank, advisor; Hein, Gary, committee member; Khosla, Rajiv, committee member; Holtzer, Thomas, committee member (Colorado State University. Libraries, 2005)
Site-specific insect management has the potential to make pest management more efficient, but has yet to be implemented. One method of implementing site-specific management would be to make decisions at the management zone level. Management zones are homogenous subregions within a field that can be managed in a similar manner. No studies have yet related insect damage to management zones. In this study site-specific management zones (SSMZ) defined by yield potential were used with the purpose of determining whether arthropod damage differs across SSMZ. The influence of water and nitrogen levels were also analyzed. The study was conducted in a com (Zea mays L.) agroecosystem at Colorado State University's Agricultural Research, Development, and Education Center (ARDEC) near Fort Collins, Colorado from 2002 to 2004. Four common arthropod pests of com were studied: European com borer (Ostrinia nubilalis [Hübner]), western com rootworm (Diabrotica virgifera virgifera [Leconte]), western bean cutworm (Richia albicosta [Smith]), and Banks grass mite (Oligonychus pratensis [Banks]). Infestations of each pest were created within each SSMZ by artificially infesting pests or manipulating natural populations. Damage for western com rootworm and Banks grass mites was greater in high yielding areas. European com borer had differential survival across SMMZ. Differences in damage for western bean cutworm were unclear. The results indicated that arthropod damage for some pests did differ among SSMZ and therefore site-specific management might be beneficial.
Keywords: entomology; agronomy